EVALUATION OF VARIOUS LIGHTWEIGHT ARMCHAIRS IN TERMS OF ERGONOMICS - Yuksel, Mehmet; Ziya Erdil, Yusuf; Kasal, Ali; Acar, Mehmet (Innovation in Woodworking Industry and Engineering design, 2020)
This study aimed to evaluate comfort level of the lightweight armchairs based on user’s feedback. For this purpose, 5 different lightweight armchairs were selected and a total of 30 healthy adult volunteers (15 males and 15 female) joined to the study. A survey composed of 10 questions based on three times interval that consist of 5, 15, and 30 minutes was applied to the volunteers. The survey concentrated to obtain subject’s feedbacks related to their body reactions while they are sitting on the armchairs by five point Likert Scale. Results were analysed statistically and according to the results, some of design criteria such as backrest form, armrest height, sitting depth, and sitting height significantly affected the comfort feeling while sitting on sample armchairs. As a conclusion, it can be said that comfort in use can be increased by consideration of ergonomic criteria in design process.